Crystal structures, phase transitions, and nuclear magnetic resonance of organic–inorganic hybrid [NH2(CH3)2]2ZnBr4 crystals. Issue 2 (4th January 2023) - Lim, Ae Ran
Abstract : Thermal ellipsoid plot (50% probability) for the [NH2 (CH3 )2 ]2 ZnBr4 structure at 300 K. Abstract : Organic–inorganic hybrid [NH2 (CH3 )2 ]2 ZnBr4 crystals were grown via slow evaporation, and their monoclinic structure was determined using single-crystal X-ray diffraction (XRD). The two phase transition temperatures at 401 K ( T C1 ) and 436 K ( T C2 ) were defined using differential scanning calorimetry and powder XRD. In the nuclear magnetic resonance spectra, a small change was observed in the 1 H chemical shifts for NH2, 13 C chemical shifts for CH3, and 14 N resonance frequency for NH2 near T C1 . 1 H spin-lattice relaxation times T 1ρ and 13 C T 1ρ for NH2 and CH3, respectively, rapidly decreased near T C1, suggesting that energy was easily transferred. NH2 in the [NH2 (CH3 )2 ] + cation was significantly influenced by the surrounding environments of 1 H and 14 N, indicating a change in the N–H⋯Br hydrogen bond with the coordination geometry of the ZnBr4 anion. These fundamental properties open efficient avenues for the development of organic–inorganic hybrids, thus qualifying them for practical applications.